The Role of Sports in Positive Youth Development: A Sociological Study Based on the Gurunagar Area - Vijisnaraj, M.; Rajeshkannan, R. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
Sustainable youth development has emerged as a critical focus in contemporary discourse in sociology. While sports are globally recognized as a catalyst for positive change, their full potential remains underutilized, leading to declining youth participation. Contributing factors include shifting social structures, lack of supportive frameworks, and the growing influence of digital media, which collectively result in non-involvement and increasing social challenges among youth. This study explores the role of sports in promoting sustainable youth development, its influence on community involvement, and the socio-economic and cultural factors affecting youth participation. It also examines strategies to strengthen youth involvement through sports. This study was conducted in Kurunagar, Jaffna Divisional Secretariat Division. Sample for this study were purposively selected and data were collected from 100 young individuals. For the purpose of collecting data, in-depth interviews, case studies, focus group discussions, and structured questionnaires were accommodated. Despite the quantitative data were examined by SPSS (Version 26), the qualitative data were thematically analyzed. Findings reveal that sports significantly contribute to developing key competencies such as time management (90%), self-confidence (87%), teamwork (89%), emotional regulation (76%), self-discipline (96%), communication (74%), and healthy lifestyle habits (93%). These factors support the holistic development of youth and strengthen their ability to involve constructively in the community. However, several barriers persist such as include an overemphasis on football, limited resources, inadequate facilities, rigid cultural norms, gender-based restrictions, lower state commitments, and negative social perceptions of sports. The study highlights the need for urgent infrastructure improvements and institutional reforms to create a more inclusive and supportive environment for sports to provide opportunities towards the positive youth development.
Keywords: Social capital; Self-empowerment; Youth participation; Socialization; Sports